Building a Cognitive Dissonance Scale and Estimating Its Psychometric Characteristics among Umm Al-Qura University Female Students - Mariam H. Al-Lihyani; Sameera M. Al-Otaibi (Sultan Qaboos University, 2015)
This study aimed at building a cognitive dissonance scale that measures the dissonance and disharmony between believes, attitudes and values. The items of the measurement were articulated to suit the research female sample. Seven factors of the cognitive dissonance were extracted through the factor analysis of the answers of the sample which consists of 1097 female students from Umm Al-Qura University. Then, the factors were named according to the items they contain as follows: The family dimension, the emotional dimension, self-compatibility dimension, control and dominance dimension, social dimension, educational dimension and discipline and behavioral commitment dimension. Factorial validity and internal consistency estimates wer acceptable. The results of the study generally show the possibility of extracting cognitive dissonance. They also show that the current scale of cognitive dissonance is valid and meets the required standard specifications. Therefore it can be used in other studies. It is also recommended that more tests be made on the results, particularly on other samples in the future.